PENGEMBANGAN FLIPBOOK OF KHULAFAURRASYIDIN LEADERSHIP SEBAGAI MEDIA UNTUK MEMAHAMI POLITIK ISLAM BAGI ANAK SEKOLAH DASAR - Iya Riyani; Utari Utari; Wanty Cahyanti; Ani Nur Aeni (FASHLUNA, 2022)
Along with the changing times that are increasingly advanced, namely with the development of increasingly sophisticated technology, the younger generation today is fast in learning the technology. Then, this research has a purpose as a means of information related to politics in an Islamic perspective to the younger generation, especially elementary school children by spurring the example and characteristics of Khulafaurrasyidin which is published in the form of a Flipbook in order to adapt to the changing times that are happening at this time, namely by take advantage of technology. In addition, this study uses a qualitative method using questionnaires and interviews. We use this technique for teachers and students. We conducted these questionnaires and interviews with teachers and students. This research also uses the Design and Development (D&D) model. Regarding the process of making the video "Khulafaurrasyidin Leadership" as a medium for understanding Islamic politics for elementary school children, starting from the design of the Flipbook, developing the contents of the Flipbook, the process of developing the Flipbook, to post-production of the Flipbook. With this flipbook, it is also hoped that students can imitate the leadership of the 4 khulafaurrayidin caliphs.